Internationalizing higher education. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2005)
Many nations are moving towards economic interdependency as the modus operandi to ensure its economic growth. The increase of transnational mergers is a testament. This fact, implies that a new kind of labour is required to function across nations and cultures. According to Tan (2003), “An emerging knowledge economy is dependent on nations that can provide the required labour force to meet the needs of an increasingly globalized economy.”